THE INTEGRATION OF HEALTH STUDENT FIELD PRACTICE IN ANTHROPOMETRY MEASUREMENT OF STUNTING CASES IN PAPUA: A CASE STUDY - Isak Jurun Hans Tukayo,; La Jumu,; Yoel Halitopo,; Sukatemin,; Edison Kabak,; Syaifoel Hardy, (International Journal of Social Science, 2022)
Five regions in Papua province, namely Jayawijaya, Tolikara, Lanny Jaya, Nduga, and Dogiyai, have a high prevalence of stunting above the national figure. As part of the national strategy, empowering health students to reduce the prevalence of stunting through anthropometric measurements is very important. The purpose of this study was to identify the practical steps of students in anthropometric activities as part of handling stunting cases in Papua. This research used a case study method with a descriptive design. The sample was stunting cases in various regions in Papua province. The method used in case identification was the Blueprint Test of case management assessment with a standard nursing process of Orlando. The data was obtained from scientific journals at Google Scholar that has a DOI (Digital Object Identifier) ​​or published in reputable journals (national or international) which were analyzed using the PICOT model. The results of the PICOT analysis showed three main problems that need to be prioritized in the involvement of practical students related to anthropometric measurements. Those problems include debriefing through training, cross-sectoral collaboration driven by the campus, and program realization. This study recommended an anthropometric measurement program for stunting cases in the form of curriculum evaluation in local content, cross-sectoral collaboration, and program implementation by considering local wisdom.